Aberrant expression of Smad4, a TGF-beta signaling molecule, in oral squamous cell carcinoma. - Anak Iamaroon (2018)
Although carcinogenesis of oral squamous cell carcinoma (OSCC) has been studied by many investigators in the past decade, the available evidence about its molecular mechanism is inconclusive. The objective of the present study was to compare expression of Smad4, a signaling molecule of the transforming growth factor beta (TGF-beta) pathway, between OSCC and normal oral mucosa. We assayed expression of Smad4 in OSCC and normal oral mucosa by performing immunohistochemistry using paraffin-embedded tissue samples. We also compared expression of Smad4 protein between OSCC lines and normal oral keratinocytes, using Western blot analysis. Smad4 expression was observed in only 60% of OSCC tissue samples, whereas it was observed in 82% of normal oral mucosa samples. Reduced Smad4 expression was clearly observed in all OSCC lines, compared with normal oral keratinocytes. These findings suggest that aberration of the TGF-beta pathway, as indicated by a reduction or absence of Smad4 expression, promotes carcinogenesis of OSCC.